Policy suggestions to deal with intimate partner violence in Pakistan (Italian Journal of Public Health, 2010)
Injury is one of the leading causes of mortality and disability in the world. It is a significant public health problem that is often over looked in the developing world. The burden of noncommunicable diseases (including injuries) is increasing and currently accounts for nearly half of the global burden of disease among all ages [1]. Five million people worldwide lose their lives annually as a result of trauma and injury [2]. Globally, among the age range of 15-44 years, the leading cause of fatal injury are traffic collisions, inter personal violence, self harm, war, drowning and exposure to fire.
Keywords: Intimate partner violence; injury; Pakistan